2003
DOI: 10.1016/j.jweia.2003.09.005
|View full text |Cite
|
Sign up to set email alerts
|

New frontiers in aerodynamic tailoring of long span bridges: an advanced analysis framework

Abstract: Significant developments in bridge aeroelastic analysis have been made utilizing realistic aerodynamic force modeling for bridges with bluff sections under turbulent winds. With these developments as a background, this paper highlights state-of-the-art developments in the aeroelastic analysis and identifies new frontiers in aerodynamic tailoring of long span bridges. Challenges in the aeroelastic analysis are pointed out that include: the modeling of aerodynamic forces excited by non-stationary wind fields suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…These numerical studies provided a basis for the empirical formula suggested by Selberg ͑1961͒ for estimating the critical flutter velocity of bridges with a flat plate section. The introduction of flutter derivatives and the development of their identification schemes through wind tunnel testing offer realistic modeling of aerodynamic forces on bluff bridge sections ͑e.g., Ukeguchi et al 1966;Sabzevari and Scanlan 1968;Scanlan and Tomko 1971;Scanlan 1978Scanlan , 1993Davenport and King 1984;Sarkar et al 1994;Jakobsen 1995;Matsumoto et al 1995;Chen and Kareem 2002͒. In recent years, multimode coupled flutter analysis frameworks have been developed for advanced prediction of coupled bridge flutter, integrating the structural characteristics of multiple modes and the experimentally obtained aerodynamic forces on bridge sections ͑e.g., Miyata et al 1994;Jones et al 1998;Chen et al 2000a, b;Chen and Kareem 2003a;Diana et al 1999͒. The solution of the equations of motion of aeroelastic bridge systems through a complex eigenvalue analysis provides information on how the self-excited forces influence modal frequencies, damping ratios, and intermodal coupling as wind velocity increases ͑e.g., Chen et al 2000a͒.…”
Section: Introductionmentioning
confidence: 99%
“…These numerical studies provided a basis for the empirical formula suggested by Selberg ͑1961͒ for estimating the critical flutter velocity of bridges with a flat plate section. The introduction of flutter derivatives and the development of their identification schemes through wind tunnel testing offer realistic modeling of aerodynamic forces on bluff bridge sections ͑e.g., Ukeguchi et al 1966;Sabzevari and Scanlan 1968;Scanlan and Tomko 1971;Scanlan 1978Scanlan , 1993Davenport and King 1984;Sarkar et al 1994;Jakobsen 1995;Matsumoto et al 1995;Chen and Kareem 2002͒. In recent years, multimode coupled flutter analysis frameworks have been developed for advanced prediction of coupled bridge flutter, integrating the structural characteristics of multiple modes and the experimentally obtained aerodynamic forces on bridge sections ͑e.g., Miyata et al 1994;Jones et al 1998;Chen et al 2000a, b;Chen and Kareem 2003a;Diana et al 1999͒. The solution of the equations of motion of aeroelastic bridge systems through a complex eigenvalue analysis provides information on how the self-excited forces influence modal frequencies, damping ratios, and intermodal coupling as wind velocity increases ͑e.g., Chen et al 2000a͒.…”
Section: Introductionmentioning
confidence: 99%
“…The first systematic framework to study bridge aeroelasticity analytically started with the pioneering works of Davenport (1962) and Scanlan (1978, 1987) concerning bridge buffeting and flutter, which led to a number of analytical developments in bridge aerodynamic/aeroelasticity using realistic aerodynamic force modeling of bridges under turbulent winds. Analytical aeroelastic analysis in both time and frequency domain is still attractive for scholars, and the results of 2D and 3D studies are comparable to the available experimental data (Chen and Kareem, 2003; Miyata, 2003; Larose and Livesey, 1997; Chen et al , 2000).…”
Section: Introductionmentioning
confidence: 75%
“…Essentially, the second group uses aero-elastic coefficients named as direct and indirect flutter derivatives (FD), see e.g. Brownjohn and Bogunovic-Jakobsen (2001) or Chen and Kareem (2003) and solves the "combined time-frequency" system by an iteration directly determining the critical velocity and the frequency of the resulting coupled heave-pitch motion. Several other solutions have been proposed by different authors.…”
Section: Introductionmentioning
confidence: 99%